Integrative genome-wide gene expression profiling of clear cell renal cell carcinoma in Czech Republic and in the United States - Wozniak, Magdalena B; Le Calvez-Kelm, Florence; Abedi-Ardekani, Behnoush; Byrnes, Graham; Durand, Geoffroy; Carreira, Christine; Michelon, Jocelyne; Janout, Vladimir; Holcatova, Ivana; Foretova, Lenka; Brisuda, Antonin; Lesueur, Fabienne; et al. (PloS one, 2013)
Gene expression microarray and next generation sequencing efforts on conventional, clear cell renal cell carcinoma (ccRCC) have been mostly performed in North American and Western European populations, while the highest incidence rates are found in Central/Eastern Europe. We conducted whole-genome expression profiling on 101 pairs of ccRCC tumours and adjacent non-tumour renal tissue from Czech patients recruited within the "K2 Study", using the Illumina HumanHT-12 v4 Expression BeadChips to explore the molecular variations underlying the biological and clinical heterogeneity of this cancer. Differential expression analysis identified 1650 significant probes (fold change ≥2 and false discovery rate <0.05) mapping to 630 up- and 720 down-regulated unique genes. We performed similar statistical analysis on the RNA sequencing data of 65 ccRCC cases from the Cancer Genome Atlas (TCGA) project and identified 60% (402) of the downregulated and 74% (469) of the upregulated genes found in the K2 series. The biological characterization of the significantly deregulated genes demonstrated involvement of downregulated genes in metabolic and catabolic processes, excretion, oxidation reduction, ion transport and response to chemical stimulus, while simultaneously upregulated genes were associated with immune and inflammatory responses, response to hypoxia, stress, wounding, vasculature development and cell activation. Furthermore, genome-wide DNA methylation analysis of 317 TCGA ccRCC/adjacent non-tumour renal tissue pairs indicated that deregulation of approximately 7% of genes could be explained by epigenetic changes. Finally, survival analysis conducted on 89 K2 and 464 TCGA cases identified 8 genes associated with differential prognostic outcomes. In conclusion, a large proportion of ccRCC molecular characteristics were common to the two populations and several may have clinical implications when validated further through large clinical cohorts.
Keywords: nádory ledvin; Spojené státy americké; Humans; lidé středního věku; analýza přežití; Oligonucleotide Array Sequence Analysis; Female; Aged; dospělí; senioři; lidé; United States; Survival Analysis; Adult; DNA Methylation; metylace DNA; ženské pohlaví; Male; Middle Aged; prognóza; stanovení celkové genové exprese; Czech Republic; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Aged, 80 and over; karcinom z renálních buněk; senioři nad 80 let; Carcinoma, Renal Cell; Gene Expression Profiling; Česká republika; mužské pohlaví; Kidney Neoplasms; Prognosis